Evaluation of the effectiveness of handwashing training given to paramedic students remotely - Oktay, Mehmet Murat; Boğan, Mustafa; Sabak, Mustafa; Gümüşboğa, Hasan (IMC Journal of Medical Science, 2021)
Background and objectives: The COVID-19 pandemic has affected face to face medical education and training activities around the world. The aim of this study was to provide remote practical handwashing training to health sciences students and to measure the effectiveness of the training provided and to create a feedback model. Methods: Students of the Paramedic department were included in the study. Two virtual classrooms were created via Zoom Video Communication system. An 11-step handwashing algorithm was developed. Two hours of remote handwashing training was given. Participants were asked to apply the handwashing application they learned at their own location and to record videos. Application videos were evaluated and scored. Results: A total of 135 Term-1 and Term 2 students of the Paramedic department participated in the study. The duration of the evaluated videos was on average 57.67 ± 12.69 (34-95) seconds. Fifty-five (40.7%) of the participants successfully completed all the steps and their average success score was 10.3 ± 0.67 (8-11). The most failure (33.3%) in the process steps was the 9th step in which the wrists are rubbed with soap. Conclusion: Suitable teaching and feedback methods are required for medical and health science students who receive education and practical training remotely from home. Ibrahim Med. Coll. J. 2021; 15(2): 18-25